Chlamydia trachomatis infection of the male genital tract: an update - Mackern Oberti, Juan Pablo (2013)
Chlamydia trachomatis (CT) is the most prevalent cause of sexually transmitted diseases. Although the prevalence of chlamydial infection is similar in men and women, current research and screening are still focused on women, who develop the most severe complications, leaving the study of male genital tract (MGT) infection underrated. Herein, we reviewed the literature on genital CT infection with special focus on the MGT. Data indicate that CT certainly infects different parts of the MGT such as the urethra, seminal vesicles, prostate, epididymis and testis. However, whether or not CT infection has detrimental effects on male fertility is still controversial. The most important features of CT infection are its chronic nature and the presence of a mild inflammation that remains subclinical in most individuals. Chlamydia antigens and pathogen recognition receptors (PRR), expressed on epithelial cells and immune cells from the MGT, have been studied in the last years. Toll-like receptor (TLR) expression has been observed in the testis, epididymis, prostate and vas deferens. It has been demonstrated that recognition of chlamydial antigens is associated with TLR2, TLR4, and possibly, other PRRs. CT recognition by PRRs induces a local production of cytokines/chemokines, which, in turn, provoke chronic inflammation that might evolve in the onset of an autoimmune process in genetically susceptible individuals. Understanding local immune response along the MGT, as well as the crosstalk between resident leukocytes, epithelial, and stromal cells, would be crucial in inducing a protective immunity, thus adding to the design of new therapeutic approaches to a Chlamydia vaccine.